2015
DOI: 10.1128/aac.04172-14
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Antibacterial Activity of the MB-1 Siderophore-Monobactam Conjugate Using an Efflux Pump Inhibitor

Abstract: Preliminary enthusiasm over the encouraging spectrum and in vitro activities of siderophore conjugates, such as MB-1, was recently tempered by unexpected variability in in vivo efficacy. The need for these conjugates to compete for iron with endogenously produced siderophores has exposed a significant liability for this novel antibacterial strategy. Here, we have exploited dependence on efflux for siderophore secretion in Pseudomonas aeruginosa and provide evidence that efflux inhibition may circumvent this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…Under extremely low iron conditions in vivo , bacterial cells will not depend on less efficient siderophore for iron acquisition, thus diminishing the MB-1 activity [11]. A subsequent study demonstrated that using an inhibitor of the efflux pump that exports pyoverdine out of cells potentiated the in vivo activity of MB-1; thus, these data substantiate the hypothesis of importance of iron-binding affinity [24]. Similarly, SMC-3176 was vulnerable to the development of the same type of resistance that is reversible with drug exposure cessation.…”
Section: Discussionsupporting
confidence: 68%
“…Under extremely low iron conditions in vivo , bacterial cells will not depend on less efficient siderophore for iron acquisition, thus diminishing the MB-1 activity [11]. A subsequent study demonstrated that using an inhibitor of the efflux pump that exports pyoverdine out of cells potentiated the in vivo activity of MB-1; thus, these data substantiate the hypothesis of importance of iron-binding affinity [24]. Similarly, SMC-3176 was vulnerable to the development of the same type of resistance that is reversible with drug exposure cessation.…”
Section: Discussionsupporting
confidence: 68%
“…Through the attachment of the ironchelating siderophore adjuvant, significantly higher intracellular drug concentrations can be achieved by hijacking the bacterial iron transport system. Several of these ␀-lactam-siderophore hybrid drugs have entered preclinical/clinical trials (232)(233)(234)(235)(236), notably the cephalosporin-catechol hybrid cefiderocol, which has advanced to and is currently in phase 3 clinical trials.…”
Section: Antibiotic Hybrid Drugs Against Antibiotic-resistant Gram-nementioning
confidence: 99%
“…Recently, siderophore-conjugated monobactam antibacterial agents, BAL30072, MB-1, MC-1, and SMC-3176 with a hydroxypyridone moiety, have been reported to show potent antibacterial activities against some MDR Gram-negative bacteria, including P. aeruginosa (19, 21, 22), but the development of MB-1 and SMC-3176 has been problematic due to a lack of correlation between in vitro activity and in vivo efficacy (21–23). …”
Section: Introductionmentioning
confidence: 99%